Socialne razmere v Mariboru med letoma 1929 in 1935 - Gostenčnik, Nina (Studia Historica Slovenica, 2016)
Social circumstances in Maribor between 1929 and 1935 were far from satisfactory. The time in question coincides with the economic depression, which brought poverty and homelessness into the city and left marks in social, cultural and other aspects of people's lives. The city municipality tried to help its citizens in many different ways. It had to deal with the depression's consequences and with the increased number of citizens due to immigrations and unemployment. The article discusses some of the measures taken to facilitate the life of people in Maribor.
Keywords: brezposelnost; družbene razmere; ekonomska kriza; Maribor; socialna pomoč; socialna varnost; socialno skrbstvo; stanovanjska politika